Abstract ID: 54 The application of the FLUKA Monte Carlo code in medical physics. (October 2017) - Battistoni, Giuseppe; Ballarini, Francesca; Bauer, Julia; Böhlen, Till; Carante, Mario Pietro; Cerutti, Francesco; Chin, Mary; Santos Augusto, Ricardo Dos; Fontana, Andrea; Embriaco, Alessia; Ferrari, Alfredo; Kozlowska, Wioletta; et al.
Abstract : Monte Carlo codes are increasingly spreading in medical physics community due to their capability of performing a detailed description of radiation transport and interaction with matter. This contribution will address the recent developments of the FLUKA code and its practical application in medical physics. FLUKA is being used in radiation therapy and nuclear medicine. At present, it is of particular interest in the context of particle therapy, thanks to the development of accurate and reliable physical models capable of handling all components of the expected radiation field. At the same time, the code can be interfaced to different radiobiological models. These features become extremely important for correctly performing not only physical but also biologically based dose calculations, especially in cases where ions heavier than protons are involved. At the same time, in order to support the application of FLUKA in hospital-based environments, the FLUKA graphical interface has been enhanced with the capability of translating CT DICOM images into voxel-based computational phantoms in a fast and well-structured way. The interface is capable of importing also radiotherapy treatment data described in DICOM RT standard. Therefore, the FLUKA code not only is a reliable instrument for the simulation of therapeutic beams, but it is also used in some of the leading European hadron therapy centers as an accurate tool for Treatment Planning verification and correction. In addition, it allows an accurate prediction of emerging secondary radiation and this is of the utmost importance in innovative areas of research aiming at in vivo treatment verification. Here we shall review the features of the FLUKA code, pointing out the recent refinements of the nuclear models, relevant for the therapeutic energy interval, which lead to an improved description of the mixed radiation field. Benchmarks against experimental data with both proton and ion beams will be shown. Examples of clinical application will be presented, together with a review of some results in medical physics research.